(y+6)/4=(y-8)/7

Simple and best practice solution for (y+6)/4=(y-8)/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+6)/4=(y-8)/7 equation:


(y+6)/4=(y-8)/7

We simplify the equation to the form, which is simple to understand
(y+6)/4=(y-8)/7

Reorder the terms in parentheses
( + 0.25y+1.5)=(y-8)/7

Remove unnecessary parentheses
+ 0.25y+1.5=(y-8)/7

Reorder the terms in parentheses
+ 0.25y+1.5=( + 0.142857142857y-1.14285714286)

Remove unnecessary parentheses
+ 0.25y+1.5=0.142857142857y-1.14285714286

We move all terms containing y to the left and all other terms to the right.
+ 0.25y-0.142857142857y=-1.14285714286-1.5

We simplify left and right side of the equation.
+ 0.107142857143y=-2.64285714286

We divide both sides of the equation by 0.107142857143 to get y.
y=-24.6666666667

See similar equations:

| 18=-6a-3a | | y+6/4=y-8/7 | | 12y+18-7y-22=46 | | 4(2x+6)=48+16 | | -9(15y)= | | 4(3x-7)=-7 | | 17x-6+3x-5=x+11+4 | | -8(2)-5y=-1 | | -4-6=5x+3-4x | | 4x+8-3x=10 | | b/5+9=6 | | -9-a/4=5 | | 12x-0.5x=220 | | 2e^1+5=6 | | 7(-8)+2y= | | 5(y-2)=2y-28 | | 9(x-6)=72 | | (-5a)(-3b)= | | 4(x+1)=2(2x+8)-12 | | 5-2x+9x=40 | | 9y-12=-14-19 | | 14x+37-8x+12=16 | | 2(k+1)=-6 | | x/4-7=5 | | -1*1= | | x+2+3x+6=12 | | (4-x)(2x+5)=0 | | 0.8=(c+6)/8 | | |x|+4=12 | | 4/5=(c+6)/8 | | -2(3s-4)-8=-2(6s+1)-2 | | n/2+3=1 |

Equations solver categories